Hyvinvointivaltio ja kielitietoisuus: hyvinvoinnin diskurssit neljän suurimman puolueen eduskuntavaaliohjelmissa - Anne-Maria Karjalainen; Milla Luodonpää-Manni; Veronika Laippala (Suomen soveltavan kielitieteen yhdistys, 2026)
In this article we study discourses concerning welfare in political texts. The material consists of programs written for parliamentary elections between 1991 and 2015 by the four largest parties in Finland. The frame of reference of this study is social constructivism. We used both quantitative and qualitative methods. First, we explored the typical phrases related to word welfare with keyword analysis. Then, these phrases were examined in more detail. The study shows that in each party’s programs two prevalent themes in terms of welfare can be found: that concerning economics and competitiveness of the state and that concerning welfare responsibility. It is also shown that each party has its own discourse within these themes. Increasing language awareness in the society is important in order to recognize the various discourses concerning the welfare state and to understand the implications that these discourses have for the development of the society.